2014
DOI: 10.1200/jco.2013.49.3676
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hospitalization According to Chemotherapy Regimen in Early-Stage Breast Cancer

Abstract: TAC and AC + T were associated with the highest risk of hospitalization in patients younger than age 65 years. Among patients older than age 65 years, all regimens (aside from dose-dense AC + P) were associated with a higher risk of hospitalization than TC. Results may be affected by selection biases where less aggressive regimens are offered to frailer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
5
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 42 publications
6
78
5
3
Order By: Relevance
“…These differences remained statistically significant, even after adjustment for a variety of other factors that might affect visit frequency. Our findings are consistent with data from Barcenas et al, 4 showing higher rates of hospitalization during AC-T and TAC. We suspect that greater outpatient health care use during and after AC-T and TAC might, in part, reflect a greater burden of toxicity among recipients of combined anthracycline and taxane therapy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These differences remained statistically significant, even after adjustment for a variety of other factors that might affect visit frequency. Our findings are consistent with data from Barcenas et al, 4 showing higher rates of hospitalization during AC-T and TAC. We suspect that greater outpatient health care use during and after AC-T and TAC might, in part, reflect a greater burden of toxicity among recipients of combined anthracycline and taxane therapy.…”
Section: Discussionsupporting
confidence: 93%
“…24 Barcenas et al 4 reported significantly higher rates of hospitalization in early stage breast cancer patients who received anthracycline-based chemotherapy than in those who received docetaxel/cyclophosphamide (TC), suggesting that TC carries less risk of acute severe toxicity. Similarly, in already-published work, our group reported higher adjusted rates of hospitalizations during the chemotherapy administration period among early stage breast cancer patients who received anthracycline-based chemotherapy compared with those who received TC.…”
Section: Introductionmentioning
confidence: 99%
“…In BC and other tumours, elderly patients have a higher risk of treatment interruption, neutropenia and hospitalization due to side effects [97] [98][99] [100]. Hospitalization is especially worrisome since it can lead to classical complications such as delirium and these can seriously impair functionality, with long term impact on both quality of life and survival [101] [102].…”
Section: Toxicitiesmentioning
confidence: 99%
“…A study of medical insurance claims patients in the United States found that, as of 2007, adjuvant tac chemotherapy was used in approximately 20% of women less than 65 years of age and in nearly 10% of women more than 65 years of age 10 ; however, fec-d use was not reported. In contrast, a population-based cohort of Canadian women treated between 2003 and 2009 reported that 55.6% received fec-d; tac use was not reported, however 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Acute and late toxicities should, therefore, affect treatment decision-making. The bcirg 001 study 6 and retrospective analyses 10 suggest that tac is associated with a significant risk of febrile neutropenia (particularly in the absence of primary g-csf support) and hospitalization. And although pacs-01 reported a relatively low incidence of febrile neutropenia 8 , retrospective studies have documented much higher rates of febrile neutropenia and hospitalization 11,12 .…”
Section: Introductionmentioning
confidence: 99%